Morphological Factors that Underlie Neural Sensitivity to Stimulation in the Retina. Issue 12 (8th December 2021) - Raghuram, Vineeth; Werginz, Paul; Fried, Shelley I.; Timko, Brian P.
Abstract : Retinal Degenerative Diseases Recent advances in retinal protheses offer new opportunities to restore sight in patients with vision loss. Shown here is a flexible, transparent and conformal epiretinal implant featuring an array of metallic stimulation pads. These pads offer spatially‐selective activation of the underlying retinal ganglion cells, offering potential for high‐resolution visual inputs. This is reported by Brian P. Timko and co‐workers in article number 2100069 .